Kekuatan Hukum Memorandum of Understanding (MoU) pada Perjanjian Pageant Miss Beauty Jatim 2022 - Fresil Nurassyafa Almayunda; Hardian Iskandar; Dodi Jaya Wardana (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The Memorandum of Understanding (MoU) is a preliminary agreement in contracts established under the Common Law system, and this research is based on the increasing phenomenon of using MoUs as an initial form of agreement in various fields, including the organization of beauty pageants; however, in practice, there remains ambiguity regarding the extent to which an MoU has binding legal force, particularly when one party commits a breach of contract or when disputes arise, thus this study formulates two main issues, namely the legal status of the parties involved in the MoU of the Miss Beauty East Java 2022 pageant agreement and the legal consequences of the non-performance of such MoU, employing a normative juridical method through statute, conceptual, and case approaches to analyze the practice of MoUs in Miss Beauty East Java 2022, and the findings indicate that although MoUs are not explicitly regulated in the Indonesian Civil Code, they may be considered preliminary agreements subject to the principle of freedom of contract under Article 1338 of the Civil Code, with the legal status of the parties being binding as long as the MoU fulfills the essential elements of a valid contract (agreement, legal capacity, specific object, and lawful cause), while the legal consequences of non performance may give rise to legal liability resolved through non-litigation efforts such as mediation or arbitration, or ultimately through litigation if amicable settlement fails, leading to the conclusion that the MoU in the Miss Beauty East Java 2022 pageant possesses binding legal force as a preliminary agreement rather than merely a moral commitment, provided that it is clearly drafted and meets the validity requirements of a contract under Indonesian law.